Effect of Various Yogic Practices on Skill Performance in Football Players - A. , Suman Kumar; Yokesh, T.P. (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study was to investigate the Effect of various yogic practices on skill performance in football players. Forty male football players participated in this study as the subject. The subjects were randomly assigned to yogic practices group (n=20, age: 15 to 17 years) and control group (n=20, age15 to 17 years). The YP group performed eight weeks’ lower extremities YP besides the football team training. The control group performed only the game practice during the study. The results showed that the speed, dribbling, agility with ball improved after PY (P